ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAJIAN LAPORAN KEUANGAN PADA SATUAN KERJA PERANGKAT DAERAH PEMERINTAH KABUPATEN MALUKU TENGGARA - Fransiskus Dempo Renwarin; Maxion Sumtaky (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2019)
This study aims to analyze the effect of Human Resources Capacity, Government Control, Utilization of Information Technology, and Regional Financial Supervision on the Timeliness of Financial Statement Presentation at the regency working unit of the Southeast Maluku Regency.. Descriptive analysis occupied to describe the formulation of the first and second problems (Sugiyono, 2010).This study also as a verification , which is used to test the allegations about the relationship between the variables of the problem being studied. Data collection using questionnaires, interviews and documentation. Data analysis instrument used multiple linear regression analysis. The results showed that the capacity of HR, Government Internal Control, and regency financial oversight did not significantly influence the Timeliness of Financial Statement Presentation in the Southeast Maluku Regency SKPD. Meanwhile, the Utilization of Information Technology has a significant effect on the Timeliness of the Presentation of Financial Statements in the SKPD of Southeast Maluku Regency.